PENGGUNAAN MEDIA PEMBELAJARAN AKSI (ANIMASI KISAH SURI TELADAN NABI) UNTUK MENUMBUHKAN NILAI MORAL SISWA KELAS IV SEKOLAH DASAR - Juliana Marchela; Lia Fitriani Trengganis; Wahyu Septi Angga; Ani Nur Aeni (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Almost all schools have held online learning since the Covid-19 pandemic. The lack of interaction between teachers and students during learning activities is exacerbated by distance learning. The purpose of this study was to determine the use of AKSI learning media in growing the moral values of fourth grade elementary school students. The D&D (Design and Development) model is used in this study. Fourth grade elementary school teachers and students were used to test the product. The majority of students gave a “good” evaluation product, according to the results. Thus, fourth grade elementary school children can use the AKSI learning media to instill moral values, and teachers who have difficulty delivering teaching materials can use it to improve the delivery of information on teaching materials.